Green BIM and CIM: Sustainable Planning Using Building Information Modelling. - Dall’O’, Giuliano; Zichi, Alessandro; Torri, Marco (Springer, 2020)
The design, construction and management of sustainable and intelligent buildings, neighbourhoods and cities require tools that can manage complexity in a completely different manner to the practices adopted to date. This chapter introduces the most advanced current approach, Building Information Modelling (BIM), focusing in particular on its use to support green and smart planning of buildings, neighbourhoods and cities. The initial part of the chapter introduces the general concepts underlying the BIM. The second part explores its application, the Green BIM, intended as the use of the tool to support the sustainable design of buildings. The chapter concludes with the introduction of a more recent concept, the City Information Modelling (CIM), intended as a common platform to design, build and manage the buildings, infrastructures and services of neighbourhoods and cities that evolve towards sustainable and smart schemes.
Keywords: Nachhaltiges Bauen; Green Building; Smart Building; Kreislaufwirtschaft; Lebenszyklus; Nachhaltige Stadtentwicklung; Building Information Modelling (BIM); City Information Modelling (CIM)